Analysis of New Paradigm Learning Activities for the 2022 School Mobilization Program - Winditiya Yuliana (Universitas Muhammadiyah Enrekang, 2022)
Changes and developments in the educational curriculum seem to be happening so fast, that it demands that we who work as lecturers who print students for prospective teacher educators must adapt to these changes, namely by increasing or developing self-competence adapted to the needs of the curriculum era implemented at the education unit level. primary school teachers. The 2030 Education Projection carried out by the OECD, based on the new learning paradigm, competencies not only focus on cognitive, attitude, and psychomotor aspects, but also values ​​that complement student competencies. Currently, the quality of literacy and numeracy, mental health and emotional social of students are the foundations or prerequisites needed by students to build students' transformative competencies with the Anticipation, Action, Reflection learning cycle towards lifelong learners. Therefore, changing the curriculum is something that naturally occurs due to changing times and changing needs in each educational unit. One of the important things in this curriculum is contextual, so that educational units can organize learning according to the needs of students.